Assessing the Cultural Appropriateness of UPLIFT for African Americans With Epilepsy: A Community Engaged Approach - Josalin Hunter-Jones; April Nellum; Elizabeth Olorundare; Candace McCloud; Matthew McCurdy; Robin McGee; Contessa Davis; Nancy Thompson; Rakale Quarells (Georgia Southern University, 2016)
Background: In trials of Project UPLIFT, a distance-delivered, mindfulness-based cognitive therapy intervention, there was improvement in the mental health of people with epilepsy/seizure disorder. In these trials, however, African Americans have been few. Thus, as this program is disseminated, it is desirable to ensure that it is culturally appropriate for minority populations. Methods: To determine the appropriateness of Project UPLIFT for African Americans, we engaged in three main research activities: 1) the formation and involvement of an epilepsy community advisory board; 2) qualitative interviews with healthcare providers who serve this community; and 3) focus groups with African American adults living with epilepsy or seizure disorder and main support persons of African American adults living with epilepsy or seizure disorder. Results: The epilepsy community advisory board provided recommendations for the most appropriate language to use when engaging and recruiting the target population. Healthcare providers indicated that psychosocial concerns of African American persons living with epilepsy seemed to be different from those among patients of other racial groups. They indicated that Project UPLIFT might be useful for this group. Focus groups revealed experiences of living with and supporting someone with epilepsy and provided favorable feedback on the UPLIFT intervention. Conclusions: Formative feedback indicates that Project UPLIFT may be useful for African Americans with epilepsy. These data will be used to guide a forthcoming randomized, controlled trial to assess the acceptability and feasibility of the intervention with this group.